Source-dependent variations in chitin: a comparative study on Antarctic krill, white shrimp and crayfish - Chenyi Yang; Xiaoyun Chen; Zuman Chen; Yadong Zhao; Ruizhi Yang; Yu Xia; Qinyi Zeng; Yanhong He; Hao Lan (Frontiers in Marine Science)
Chitin, the second most abundant biopolymer in nature after cellulose, has a diverse array of applications in the pharmaceutical, medical, agricultural, textile, cosmetic, wastewater treatment, and food industries. This versatility is attributed to its essential functional properties, including biodegradability, biocompatibility, and non-toxicity. The primary source of commercial chitin is the shells of crustaceans. However, the quantity and quality of chitin extracted from various crustacean shells have not yet been systematically reported or compared. In this study, we compared the composition of three types of crustacean shells: Antarctic krill (AK), White shrimp (WS), and Crayfish (CF). We employed a consistent sequence of deproteinization, decalcification, and bleaching to extract chitin from these shells. The extracted chitin was characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), thermogravimetric analysis, and scanning electron microscopy (SEM). Our findings indicated that the chitin content in Antarctic krill reached 24.06%, significantly exceeding that of the other two crustaceans. Notably, scanning electron microscopy (SEM) characterization confirmed that chitin samples from different biological sources exhibit significant structural heterogeneity. This study, through multidimensional morphological analysis, provides critical experimental evidence for both the targeted synthesis of chitin-based functional materials and the high-value-added conversion of crustacean-derived by-products.